Helicobacter pylori neutrophil-activating protein: a potential Treg modulator suppressing allergic asthma? - Sehrawat, Anjna; Sinha, Siddharth; Saxena, Abhishek (Frontiers in Microbiology, 2015)
The ultimate aim of immunology is to kill the pathogen without being harmful to the host. But what if eliminating the pathogen in itself is discomforting for the host? One such emerging case is of Helicobacter pylori. Modern medicine, infantile vaccination and ultra-hygienic conditions have led to progressive disappearance of H. pylori in different parts of the world. However, the adversities caused by H. pylori’s absence are much larger than those caused by its presence. Asthma is rising as an epidemic in last few decades and several reports suggest an inverse-relationship between H. pylori’s persistence and early-life onset asthma. Regulatory T cells play an important role in both the cases. This is further supported by experiments on mouse-models. Hence, need of the hour is to discern the relationship between H. pylori and its host and eliminating its negative impacts without disturbing our indigenous microbiota. To resolve whether H. pylori is a pathogen or an amphibiont is another important side. This review explores the biological basis of H. pylori-induced priming of immune system offering resistance to childhood-onset asthma. HP-NAP-Tregs interaction has been predicted using molecular docking and dynamic simulation.